Efisiensi Perbankan Syariah Di Indonesia Dengan Stochasitic Frontier Analysis (SFA) - Duwi Setiyani; Lorena Dara Putri Karsono (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to examine the effect of Total Assets, Third Party Funds and Operating Costs on Total financing and measure the efficiency level of Bank Aladin Syariah in the 2020-2022 period. This research uses a quantitative approach with a causal associative research type. The data used in this study comes from the financial statements of Bank Aladin Syariah. The results showed that partially Total Assets had a significant effect on Total Financing of Bank Aladin Syariah. While Third Party Funds and Operating Costs have no effect on Total Financing. The highest efficiency value of Bank Aladin Syariah according to the Stochastic Frontier Analysis method occurred in the 2022 period. The implication of the research results is that the Bank Aladin Syariah policy improves its operational performance by being able to rationalize its operating costs. The highest efficiency value in 2022, the bank can concentrate policies by maintaining and improving efficiency through sustainable policies, regular evaluation, and adaptation to changes in the business environment. Bank Aladin Syariah can ensure the sustainability and improvement of its operational performance